Expression of c-fos protooncogene in normal human peripheral blood granulocytes (The Rockefeller University Press, 1987)
We have investigated by Northern blot analysis the expression of c-fos protooncogene in human peripheral blood polymorphonuclear leukocytes (PMN). Freshly isolated PMN, unlike highly purified circulating lymphoid cells, showed high levels of c-fos transcripts. Appreciable c- fos mRNA was detected in monocytes, but in lesser amounts compared with PMN. Upon exposure to a series of agents that functionally stimulate granulocytes (PMA, inactivated streptococci, TNF, granulocyte and granulocyte/macrophage colony-stimulating factor), a considerable increase in c-fos transcripts was detected. Expression of c-fos in PMN was superinduced by exposure to cycloheximide. These data indicate that the myelomonocytic differentiation pathway c-fos expression is not peculiar to monocytes/macrophages and that PMN may represent a suitable system with which to investigate the link between protooncogene expression and functional activation.